Assessment of slope hazards affected by tree root system - Solahuddin, Daud (2025)
This study investigates unmanned aerial vehicles (UAVs) used for slope mapping and hazard assessment. UAVs provide high-resolution imagery crucial for creating detailed mapping outputs, such as digital elevation models (DEM) and orthophotos. The study employs various methods, including laboratory work consisting of soil classification tests, shear strength tests on soil samples, and fieldwork incorporating electrical resistivity imaging (ERI) and ground penetrating radar (GPR) to map tree root systems. Besides that, this study also presents a comparative analysis of electrical resistivity imaging (ERI) and ground penetrating radar (GPR) in tree root system mapping, which aims to evaluate and identify the limitations and potential workability of these both equipment. The study successfully identifies potential slope hazards based on slope angles (°) and classifies slope conditions. A slope stability analysis using SLOPE/W and manual sheet calculation, incorporating tree root factors, shows that slopes with trees have an 8.41% higher factor of safety (FOS) compared to those without trees. The results highlight the value of combining UAV-derived data with SLOPE/W for geotechnical mapping and hazard identification. Overall, the study demonstrates the importance of modern technology, such as UAVs, in geotechnical engineering for early hazard detection, preventing potential risks, and ensuring safety. Other than that, the combination of ERI and GPR surveys proved to be a practical approach for mapping tree root systems as a non-invasive process to identify the distribution of tree roots associated with slope stability assessment.